ANALYSIS OF THE DEVELOPMENT AND ECONOMIC POTENTIAL OF TOURISM SERVICES IN THE REPUBLIC OF KARAKALPAKSTAN - Madaminova Sanabar Askarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article analyzes the current trends in the development of tourism services in the Republic of Karakalpakstan. In particular, it covers the content of the projects being implemented to expand the tourism potential of the region and develop new tourism facilities. Also, based on a study of the indicators of foreign and domestic tourists visiting the Republic of Karakalpakstan and the export of tourism services, reasonable proposals and recommendations are given to increase the economic potential of tourism services in the region.